The Impact of Visual Design on Impulse Buying in Shopee's Instagram Ads - Fricillia, Michelle; Julianto, I Nyoman Larry; Maharani, Ida Ayu Dyah (Universitas Ciputra, 2025)
This research examines how visual design elements in Shopee’s Instagram advertisements influence consumers’ impulsive buying behavior. With the growing prevalence of online shopping among users aged 18 to 34, brands increasingly rely on visual strategies such as bright colors, countdown timers, and expressive illustrations to attract immediate attention. The study applies a qualitative approach using content and semiotic analysis of Shopee’s “6.6 Campaign” advertisements. The analysis focuses on color schemes, typography, illustration style, layout, and motion effects. The findings reveal that warm orange tones, bold typography, and cheerful character illustrations effectively capture attention and create a sense of urgency, which encourages spontaneous purchases. Structured layouts and balanced visual rhythm further strengthen clarity and brand recall. The results suggest that combining emotional triggers with consistent visual identity enhances user engagement and purchase intention. This study underscores the role of visual communication design as a strategic tool in shaping consumer perception and behavior in digital commerce.